2017
DOI: 10.17711/sm.0185-3325.2017.007
|View full text |Cite
|
Sign up to set email alerts
|

Distress and its association with self-care in people with type 2 diabetes

Abstract: Introduction. Low adherence to diabetes self-care affects glycemic control and increases the risk of diabetes complications and premature deaths. Studies from the United States have found a relationship between distress and adherence to self-care in patients with diabetes; however, there is a lack of research on distress and its association with self-care in Mexican patients with diabetes. Objective. To evaluate the prevalence and association of distress with low self-care in patients with type 2 diabetes. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
3
0
3
Order By: Relevance
“…The higher rate of psychological distress among our study population might be due to the demographic differences and the increasing challenges related to globalization and socioeconomic alterations in the studied region [ 29 ]. Moreover, in line with previous studies, our findings demonstrated that patients with higher self-care scores had significantly lower psychological distress levels; however, previous studies associating self-care with psychological distress were mostly about other conditions including diabetes and ischemic heart diseases [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…The higher rate of psychological distress among our study population might be due to the demographic differences and the increasing challenges related to globalization and socioeconomic alterations in the studied region [ 29 ]. Moreover, in line with previous studies, our findings demonstrated that patients with higher self-care scores had significantly lower psychological distress levels; however, previous studies associating self-care with psychological distress were mostly about other conditions including diabetes and ischemic heart diseases [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is important for nurses to continuously evaluate patient psychological reaction to disease management because changes associated with the diagnosis of diabetes may lead to psychological effects such as depression (Egede & Ellis, 2010) and negative coping style (Shayeghian, Hassanabadi, Aguilar-Vafaie, Amiri, & Besharat, 2016). In addition, psychological distress may then cause poor adherence to medication and physical activity recommendations (Martinez-Vega, Doubova, & Perez-Cuevas, 2017). To support effective disease self-management, it is imperative nurses do not underestimate the emotional changes that may arise with diagnosis and intentionally assess patient psychological state at each follow-up appointment.…”
Section: Discussionmentioning
confidence: 99%
“…Por ello, es fundamental contar con apoyo psicológico para manejar estas asociaciones y promover el autocuidado. 13 Una evolución favorable para el paciente con diabetes mellitus va a depender mucho de la voluntad, compromiso y disciplina desde que comienza su plan de tratamiento. El profesional de salud va a personalizar una terapia adecuada de acuerdo a las condiciones fisiológicas del paciente, donde se dará una alternativa farmacológica como la metformina o no farmacológica que intervine de la dieta y el ejercicio.…”
Section: Introductionunclassified